Association between vitamin D deﬁciency and cognitive function in the elderly patient in a tertiary care hospital, Bangladesh (Bangladesh Journal of Medicine, 2026)
Background: Recent research has shown vitamin D deficiency as a risk factor for cognitive impairment. The study's objective was to determine the association between vitamin D insufficiency and cognitive function in the elderly patient. Methods: This case control study was conducted in the department of neurology, Sir Salimullah Medical College, Mitford, Dhaka, Bangladesh from July 2022 to June 2023. Fifty cognitive impairment patients and 50 matched healthy control subjects were participated in the study. We evaluated subjects with cognitive function with available serum Vitamin D [2S (OH) D] levels. Descriptive statistics means and standard deviations and logistic regression analyses were performed by SPSS 25. Results: The mean age of patients was 70.7 +/-6.3 years and the control was 61.480 +/-7.15 years (p =0.613). Twenty-three subjects (46%) had severe cognitive impairment (SCI); 16 (32%) moderate cognitive impairment (MoCI); and 11 (22%) mild cognitive impairment (MCI). The overall prevalence of severe Vitamin D deficiency was 76%, being more frequent in the severe cognitive impairment group (47.4%), followed by the moderate cognitive (31.6%) and the MCI (21%) (p < 0.001) groups. Executive function was measured by the Clinical Dementia Rating (CDR) (6.2+/- 1.01, 3.8+/-1.0, 2.3+/-0.5; p =